Type 2 Diabetes Mellitus is the Risk Factor for Multi-drug Resistance Tuberculosis: A Meta-Analysis - Bibit Irawan; Farit Setyo Nugroho; Nine Elissa Maharani (Masters Program in Public Health, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) has a significant risk of developing active Tuber-culosis (TB) and complicates its treatment. There is no conclusive evidence on whether TB-T2DM comorbidities are associated with an increased risk of Multidrug Resistant Tuberculosis (MDR-TB). The study aims to analyze and estimate the relationship of T2DM to MDR-TB incidence and to estimate the size of the combined effect. Subjects and Method: This study was a meta-analysis with PICO, Population: patients actively undergoing MDR-TB treatment. Intervention: Patients with comorbid Type 2 Diabetes Mellitus. Comparison: Tuberculosis patients without comorbid Type 2 diabetes mellitus. Output: MDR-TB (Multidrug Resistant Tuberculosis). The articles used in this study were obtained from databases with keywords to search for articles were (